Paciente de sexo femenino de 76 años de edad con obesidad y diabetes mellitus tipo 2. - Oviedo Pulecio, Neptali Fulton (2021)
Type II diabetes mellitus is a pathology that seriously affects Ecuador, being the third cause of death in the country, an indicator that should promote the population to have a better food quality and avoid suffering from this disease. The patient to be treated was a 76-year-old female with a weight of 82 kg and a height of 1.53 meters. The patient was diagnosed with type 2 diabetes mellitus 6 years ago. She goes to the endocrinology office because she has been feeling unwell lately, has signs and symptoms such as chronic evolution, asthenia, irritability, evening edema of grade 1 lower edema, chronic constipation, hair loss, brittle nails, maintains acceptable metabolic control (hemoglobin 7.2 %) treated with oral antidiabetic drugs metformin 850. The patient needs to apply nutritional therapy in order to solve his problem, which will be adequate for the needs of the individual and control of the pathology; with the purpose of avoiding the worsening and suffering of possible complications such as nephropathy, retinopathy, among others.